Peer Support, Confidence, Perceived Stressors, and Academic Performance among Bachelor of Science in Nursing Students - Henry See; Edzen Espina; Nenita I. Prado (Asian Journal of Education and Social Studies, 2026)
Academic performance among nursing students is associated with various psychosocial factors that shape their learning experiences and educational outcomes. Hence, this study examined the relationships of peer support, confidence, and perceived stressors with the academic performance of Bachelor of Science in Nursing (BSN) students in selected higher education institutions in Davao del Sur. Using a descriptive-regression research design, data were collected from 317 BSN students through proportionate stratified random sampling. Results revealed that students reported a high level of peer support, with interaction obtaining the highest rating and inclusivity the lowest. They also demonstrated a high level of confidence across self-assurance, belief, resilience, and competence. Perceived stressors were likewise rated high, with workload identified as the most prominent stressor. Students demonstrated very satisfactory academic performance. Pearson correlation analysis showed weak but statistically significant negative relationships between academic performance and overall peer support, collaboration, inclusivity, and workload. Multiple regression analysis further revealed that the model significantly predicted academic performance. Among the predictors, competence was a significant positive predictor, whereas encouragement was a significant negative predictor. These findings highlight the importance of strengthening students’ competence and further examining the unexpected negative association between peer encouragement and academic performance among BSN students.